Potensi Pengembangan Kawasan MOI sebagai RTH Hutan Kota dan Kawasan Agroeduwisata Perkotaan - Andry S; Devi Triana; Rivananda Rivananda; Hari Iswoyo (Hasanuddin Student Journal, 2017)
Abstract: RTH or also called green open space is an open space without a building, having certainsize, shape, and geographical boundaries with any status of mastery, in which there are woodyand annual green plants, with trees as the main plant and other plants (shrubs, grasses and othercover plants), as complementary plants and other objects that also complement and support thefunctions of the respective green space. RTH and urban forest found in the city of Makassar hasdecreased and not functioned optimally. In addition, RTH in the city of Makassar has not providedan educational function. Therefore, RTH in Makassar city needs to be developed by creating anarea such as agro-tourism area. One of location that has good potential and has been developedas one of the green open space and urban forest in Makassar is Maccini Sombala Site. MacciniSombala is an area located on Nuri Baru sub-district Tamalate of Makassar. Therefore, a MOIplanning concept is created as an agro-tourism area. This research aims to make MOI areaplanning as edu-agro-tourism area. The usefulness of this research is a consideration for thegovernment in the development of the area and other areas with other similar functions. Theresearch method used is the site design modification that leads to the concept of MOI areaplanning as edu-agro-tourism area.Keywords: RTH, urban forest, Maccini Somabala, edu-agro-tourism area